HUNTING IN RURAL AREAS OF BACKA - Prentović, Risto; Kurjački, Arsen; Cvijanović, Drago (Economics of Agriculture, 2012)
The aim of the study was to determine whether hunting, and with which activities in the rural areas, correlate, and whether, as such, may contribute to the development of rural communities in Backa. The used methods in this paper are: fieldwork (systematic observation and interviews), analysis (literature and documentation) of content and statistical methods. The study also revealed that hunting, which is located entirely in rural areas, which are, in fact, the only hunting areas and hunting wildlife habitats, is important and profitable area of business, and that hunting tourism, as the most propulsive part of hunting, is in the correlation and complementary relationship to rural tourism in Backa. To achieve even better integration of hunting in the rural development of Backa, it is necessary to prevent and eliminate the effects of certain limiting factors.